Global cancer statistics for children: Two decades of change and projections to 2050 - Wangzhong Li; Shanzhou Huang; Qiyue Chen; Ting Wang; Guanming Lu; Xing Niu; Qiong Song; Yilin Xu; Ke Mo; Chunhui Cui; Run Zhang; Wei Du; et al. (CA: A Cancer Journal for Clinicians, 2026)
Abstract Reliable, contemporary estimates of the global childhood cancer burden remain scarce, particularly in the post‐coronavirus disease 2019 (COVID‐19) era. By using data from the Global Burden of Disease 2021 and Global Cancer Observatory 2022 projects, the authors evaluated the childhood cancer burden at global, regional, and national levels, characterizing temporal and projected trends, and analyzed the data according to disparities by geography and socioeconomic development. From 2000 to 2021, the age‐standardized incidence rate (ASIR) and the age‐standardized mortality rate (ASMR) of childhood cancer declined overall (average annual percent change, −0.88 and −2.13, respectively), especially during the COVID‐19 pandemic. During this period, the disparities in childhood cancer burden were mainly concentrated in countries/territories with a lower Sociodemographic Index. In 2022, an estimated 202,164 new cases and 77,182 deaths from childhood cancer occurred worldwide (ASIR and ASMR, 10.3 and 3.9 per 100,000 children, respectively). Countries/territories with higher a Human Development Index (HDI) had a higher incidence (ASIR, 8.0 [low HDI] vs. 15.3 [very high HDI] per 100,000), whereas those with a lower HDI had higher mortality (ASMR, 4.4 [low HDI] vs. 2.8 [very high HDI] per 100,000). Analyses indicated that, by 2050, there will be 204,925 projected new cases and 78,210 deaths globally, with increases only in low HDI countries/territories, exacerbating existing health inequities. Childhood cancer remains a global health challenge, with notable geographic and socioeconomic disparities. These data serve as the impetus for governments and policymakers to prioritize resources and equitable access to interventions, particularly in regions with lower levels of development, while addressing health care vulnerabilities exposed by global crises like the COVID‐19 pandemic.